In vitro degradation and mechanical properties of PLA-PCL copolymer unit cell scaffolds generated by two-photon polymerization - Felfel, R.M.; Poocza, Leander; Gimeno-Fabra, Miquel; Milde, Tobias; Hildebrand, Gerhard; Ahmed, Ifty; Scotchford, Colin; Sottile, Virginie; Grant, David M.; Liefeith, Klaus (IOP Publishing, 2016)
The manufacture of 3D scaffolds with specific controlled porous architecture, defined microstructure and an adjustable degradation profile was achieved using two-photon polymerization (TPP) with a size of 2  ×  4  ×  2 mm3. Scaffolds made from poly(D,L-lactide-co-ɛ-caprolactone) copolymer with varying lactic acid (LA) and ɛ -caprolactone (CL) ratios (LC16:4, 18:2 and 9:1) were generated via ring-opening-polymerization and photoactivation. The reactivity was quantified using photo-DSC, yielding a double bond conversion ranging from 70% to 90%. The pore sizes for all LC scaffolds were see 300 μm and throat sizes varied from 152 to 177 μm. In vitro degradation was conducted at different temperatures; 37, 50 and 65 °C. Change in compressive properties immersed at 37 °C over time was also measured. Variations in thermal, degradation and mechanical properties of the LC scaffolds were related to the LA/CL ratio. Scaffold LC16:4 showed significantly lower glass transition temperature (T g) (4.8 °C) in comparison with the LC 18:2 and 9:1 (see 32 °C). Rates of mass loss for the LC16:4 scaffolds at all temperatures were significantly lower than that for LC18:2 and 9:1. The degradation activation energies for scaffold materials ranged from 82.7 to 94.9 kJ mol−1. A prediction for degradation time was applied through a correlation between long-term degradation studies at 37 °C and short-term studies at elevated temperatures (50 and 65 °C) using the half-life of mass loss (Time (M1/2)) parameter. However, the initial compressive moduli for LC18:2 and 9:1 scaffolds were 7 to 14 times higher than LC16:4 (see 0.27) which was suggested to be due to its higher CL content (20%). All scaffolds showed a gradual loss in their compressive strength and modulus over time as a result of progressive mass loss over time. The manufacturing process utilized and the scaffolds produced have potential for use in tissue engineering and regenerative medicine applications.